The Effect of Adding Chitosan as a Commercial Coagulant Aid in Reducing Microplastics in Leachate: Pengaruh Penambahan Kitosan sebagai Bantuan Koagulan Komersial dalam Menurunkan Mikroplastik Pada Air Lindi - Hasna Aqilah Putri Agdy; Okik Hendriyanto Cahyonugroho; Praditya Sigit Ardisty Sitogasa (​Institute for Researches and Community Services Universitas Muhammadiyah Palangkaraya, 2026)
Leachate from the final processing site (TPA) has the potential to pollute the environment because it contains organic compounds, suspended solids, and microplastics. This study aims to analyze the effect of varying doses of polyaluminum chloride (PAC) coagulant and chitosan on the reduction of microplastics, COD, and TSS in leachate from the Randegan landfill. The method used was coagulation-flocculation with a jar test. The results showed that varying doses and combinations of coagulants affected the effectiveness of treatment. The combination of PAC and chitosan at the optimum dosage was able to reduce microplastics by 78%, COD by 86%, and TSS by 91%. The reduction in microplastics occurred through the mechanisms of charge neutralization, adsorption, and sweep flocculation. The combination of PAC and chitosan has the potential to be applied as an effective and sustainable leachate treatment method.